Atmospheric implications of hydration on the formation of methanesulfonic acid and methylamine clusters: A theoretical study. (April 2020) - Chen, Dongping; Li, Danfeng; Wang, Changwei; Luo, Yi; Liu, Fengyi; Wang, Wenliang
Abstract: The effect of hydration on the formation mechanism of clusters consisting of methanesulfonic acid (MSA) and methylamine (MA) is investigated by quantum chemistry (Density Functional Theory, DFT) and kinetics simulation (Atmospheric Chemical Dynamic Code, ACDC) methods. The results showed that the process of hydration is favorable from the thermodynamic point of view, and the presence of water molecules can promote proton transfer significantly. Although MA has a significant influence on the formation rate of MSA-based clusters at the parts per trillion (ppt) levels, the effective nucleation of MSA-MA anhydrous clusters hardly seems to occur under common typical atmospheric conditions. The high concentrations of precursors ([MSA] > 6 × 10 7 molecules·cm −3 and [MA] > 1 ppt or [MSA] > 1 × 10 6 molecules·cm −3 and [MA] > 100 ppt) is necessary for the effective nucleation of the MSA-MA system. The formation rate of the MSA-MA system is enhanced significantly by hydration. The formation rate increases with the relative humidity (RH) and reached up to a factor of 2700 at RH = 40%. The formation mechanism of the hydrous system is different from the anhydrous system. The formation of (MSA)2 and (MSA)(MA) dimers is the rate-determining step of the anhydrous and hydrous systems, respectively. In addition, the growth pathway of clusters was complicated by low temperature and simplified by high humidity, respectively. In general, although humidity is a very favorable factor for the formation of the MSA-MA system, the involvement of other species (such as sulfuric acid) may be more effective to promote the nucleation of the MSA-MA system under typical atmospheric environment. Highlights: Hydration can promote significantly proton transfer in the MSA-MA clusters. Effective nucleation is difficult to occur under typical atmospheric conditions. Formation rate increases with RH and reaches a maximum of 2700 at RH = 40%. Formation of (MSA)2 is a rate-determining step in cluster growth at anhydrous condition. Formation of (MSA)(MA) dimer is a rate-determining step in cluster growth at hydration condition.